INTEGRASI EMPAT PILAR PENDIDIKAN (UNESCO) DAN TIGA PILAR PENDIDIKAN ISLAM - LAKSANA, SIGIT DWI (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2016)
Education cannot be discharged in human life. All requiring education to realize what have been created. Education which have been woke up and designed have to be sturdy and do not be groggy easy to, education building have to tighten with strong pillars. UNESCO as institute of PBB which active in education, science, and culture have formulated four education pillar, this matter is meant to be target of education earn form. In education of Islam also have education foundation which also strength which is often referred as by three education pillar. Integrate between both the pillar building can make education in indonesia specially education of Islam can walk better and as according to teachings of Islam and nation aspiration. Keywords: integration, four education pillars, three pillars of Islamic education